Has COVID-19 lowered physical activity practice while boosting online searches for professional exercise information? - Márcio Roberto Doro; Iago Portolani de Araújo; Jeferson Oliveira Santana; João Gabriel Oliveira Doro; Priscila Teixeira João; Leonardo Cesar das Virgens; Francisco Luciano Pontes Júnior; Érico Caperuto; Daniel Leite Portella (PAGEPress Publications, 2023)
COVID-19 is an infectious and contagious disease, caused by the SARS-CoV-2 virus. Due to the rapid spreading of the virus and its lethal consequences, the WHO declared a pandemic. One of the main strategies to treat and prevent the spreading was the stay home safe, a social isolation situation that was accompanied by the closing of fitness gyms, city parks and facilities proper to exercise. This context promoted an increase in home fitness programs and in the search for information online regarding exercise and health. So, the objective of this study was to understand the effects of the pandemic on physical activity behavior and online information search regarding exercise programs. Data collection was through a google forms questionnaire, all procedures were approved by the University ethics committee and we collected data from 1065 participants. Our results showed that the participants main behavior was maintained, 80.7% of our sample were active before the pandemic and only 9.7% of this group stopped being active. On the other hand we registered 7% of participants that started exercise after the pandemic installation. Information about exercise was searched outside social media by 49.6% of the participants with 32.5% using social media. 56.1% would look only for professional advice, interestingly 11.4% of the participants were active without any kind of advice. We concluded that Covid-19 pandemic installation affected negatively the population physical activity behavior and increased awareness about the importance of exercise as a health strategy.